The RepA repressor can act as a transcriptional activator by inducing DNA bends. - Pérez-Martín, J (1991)
We have shown that a transcriptional repressor protein can regulate promoter activity via DNA bending by using the pLS1 plasmid promoter PII (which has intrinsic curvature upstream of its -35 box) and the plasmid-encoded repressor protein RepA (which strongly bends DNA). Substitution of the curved region for a straight DNA fragment containing the RepA target resulted in increased (or decreased) gene expression when RepA was supplied in trans: enhanced gene expression was evident when the target of RepA and the promoter were on the same face of the DNA helix; repression was found when they were on opposite faces of the DNA. In vitro activation of transcription from PII was observed when supercoiled DNA was used as template, but not with linear molecules. We propose that promoter activity can be regulated by the proper positioning (in or out of phase) of an induced DNA bend with the RNA polymerase recognition sites.